Conceptual Design and Analysis of a Shrouded-Type Wind Turbine for Low Wind Speed Condition - Syed Ahmad, Syed Nazim; Rosly, Nurhayati (Progress in Aerospace and Aviation Technology, 2025)
Wind energy represents a valuable renewable resource with significant potential for electrical power generation. While conventional wind turbines have been well-developed for electricity generation, they suffer from reduced efficiency and limited power output in remote areas with low wind speeds (typically below 7 m/s), where wind energy extraction becomes economically unviable. The central research question addressed in this study is: Can shrouded wind turbine technology significantly improve power generation efficiency compared to conventional open rotor designs under low wind speed conditions? This study aimed to propose a conceptual design of a shrouded wind turbine and analyze its performance under low wind speed conditions ranging from 4 to 7 m/s. The proposed wind turbine's performance was analyzed through extensive computational fluid dynamics (CFD) simulations using ANSYS Fluent. Key performance parameters, including power coefficient (Cp), tip speed ratio (TSR), velocity distribution, pressure characteristics, torque generation, and power output capabilities, were investigated. Results demonstrated that the shrouded wind turbine achieved higher Cp values at elevated tip speed ratios compared to conventional open rotor configurations. Specifically, the shrouded design generated 17.1% more power at 4 m/s and 5.0% more power at 7 m/s wind speeds. The shrouded configuration increased air velocity by 11.6% at 4 m/s and 7.5% at 7 m/s compared to the open rotor design, demonstrating enhanced wind energy capture efficiency in low wind speed environments.